(untitled) (Journal of Biomedical Investigation, 2015)
BACKGROUND: With the appreciable rise in longevity of people living with HIV/AIDS (PLWHA), the need to investigate their quality of life (QOL) has become increasingly important. OBJECTIVE: This study aimed at assessing the QOL of PLWHA attending anti-retroviral (ARV) clinics in Nnewi North Local Government Area of Anambra State, Nigeria. METHODS: The research design for this study was survey. A consecutive non-probability technique was used to recruit 388 PLWHA (113 males and 275 females) for the study. The WHOQOL-HIV Bref was used to obtain data. Subjects’ socio-demographic information was obtained using a structured questionnaire. RESULTS: A significant correlation was found between marital status, age and level of education, between level of independence and age, psychological health and level of education, and social relationship and spiritual/religion/ personal beliefs. The overall mean scores in the two domains of physical health (15.3£3.4) and spiritual/religion/personal beliefs (15.5+3.2) were found to be high. Lower QOL mean scores were observed in social relationships (13.9+3.3). No significant difference was found between males and females in all the domains of the WHOQOL- HIV Bref. CONCLUSIONS: Discrimination as well as poor living conditions may have an effect on the QOL of PLWHA. Marital and educational status may influence social relationship, spiritual/religion/personal beliefs, and psychological health of PLWHA positively.